Women’s Rights and the Archive of the All India Women’s Conference: Unearthing the Role of Women's Organizations in India's Struggle for Independence (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The nineteenth century socio- religious reform movement in India produced long term results in terms of opening up more avenues for greater women role and in shaping the anti-colonial stance of the next century. In the first half of the twentieth century the imperial rule was being challenged and was ultimately thrown out of India. The sparks of protest generated in the beginning of the twentieth century had attained huge proportions in fifty years leading to the smoldering of the Indian national movement against colonial domination. The role of women during these eventful years was not to be belittled although it has not received the importance that is its due. In the male dominated political scenario a few women emerged as shooting stars and made a place for women and their problems in a largely nationalistic scenario. These were the pallbearers of future women’s movements, like Sarojini Naidu, Annie Besant, Muthulaxmi Reddy, H.A. Tata, Hansa Mehta, Rani Laxmibai Rajwade, Rajkumari Amrit Kaur and Aruna Asaf Ali, to name a few who became dominant players and this is no mean achievement.However the prominence of a few well-known figures is a poor index of judgment to show the extent to which even the common women were involved in transcending the barriers to lift the self from the downtrodden state to which posterity had pushed them into. In this context it would be apt to highlight the fact that this was the period when women’s organizations came up and gave a collective voice to the womenfolk of India. This paper tries to bring out the role of the All India Women’s Conference established in 1927 and registered in 1930, in helping women to raise themselves from a position of neglect and disrepute to which history had relegated them.